Influence of Learning Method and Motor Ability to Learning Results Basic Motion Skills of Slow Learners (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
This research aimed to (1) analyze the effect between remedial commando method and peer teaching commando method toward learning outcome of basic movement ability of slow learners; (2) analyze the effect between students with high and low ability toward learning outcome of basic movement ability of slow learners; (3) analyze interaction between learning methods and motor ability toward learning outcome of basic movement ability of slow learners. This research used experimental design method with two treatments model and each treatment has two level as attributes. The sampling technique was total sampling and got 22 students as sample. The analyzing technique in this study was Anova two-tailed used SPSS 16.0 and significance level Î± =0.05 and also Tuckey test. The result of this research showed (1) in general can be said that learning methods and motor ability are an element that effect to learning outcome of basic movement ability of slow learners, (2) remedial commando method gives better effect to learning outcome of basic movement ability of slow learners, (3) the enhancement of basic movement ability learning outcome with applying remedial commando method and peer teaching commando, also effected by motor ability level. The level of motor ability is needed to support the learning result of basic movement ability of slow learners.